Lipase-catalyzed selective benzoylation of 1,2-diols with vinyl benzoate in organic solvents - P. Ciuffreda; L. Alessandrini; G. Terraneo; E. Santaniello (Tetrahedron: Asymmetry, 2003)
Lipases from Mucor miehei (MML) and Candida antarctica (CAL) are able to catalyze the benzoylation of the primary hydroxy group of 1.2-diols with vinyl benzoate in organic solvents. We have studied the MML-catalyzed benzoylation that proceeds with high regioselectivity and moderate enantioselectivity, whereas in the dibenzoylation reaction activity of MML and stereoselectivity of the enzymatic process is strongly influenced by steric factors.